Protective roles of apremilast via Sirtuin 1 in atherosclerosis. Issue 5 (2nd May 2022) - Sui, Dongkui; Yu, Hua
ABSTRACT: Atherosclerosis is an inflammatory disease with a high level of cholesterol in the blood. Apremilast is a new anti-inflammatory drug that possesses a potential anti-atherosclerosis effect. RT-qPCR and western blot were undertaken to assay the levels of Sirtuin 1 (SIRT1), oxidized low density lipoprotein receptor 1 (LOX-1), and CD36 molecule (CD36). Reactive oxygen species (ROS) levels were evaluated by 2', 7'-dichlorodihydrofluorescein diacetate (DCFH-DA) staining, and Oil Red O staining was performed to show lipid accumulation. The result showed that apremilast treatment reduced the expression levels of pro-inflammatory factors and p-p65, as well as lipid accumulation. Meanwhile, triglyceride (TG), total cholesterol (TC) and free cholesterol (FC) levels declined in oxidized low density lipoprotein (ox-LDL)-treated macrophages. Mechanistically, apremilast targets SIRT1 and increases SIRT1 expression. The efficacy of apremilast on inflammatory response and lipid formation required the involvement of SIRT1. Additionally, apremilast treatment reduced scavenger receptors, LOX-1, and CD36 levels. These findings suggest the protective effects of apremilast via SIRT1 in atherogenesis and highlight the need for translational research from bench to bedside. Graphical Abstract: uf0001